2014
DOI: 10.3109/15563650.2014.932366
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of convallatoxin using five digoxin immunoassays

Abstract: CONTEXT Cardiac glycosides of plant origin are implicated in toxic ingestions that may result in hospitalization and are potentially lethal. The utility of commonly available digoxin serum assays for detecting foxglove and oleander ingestion has been demonstrated, but no studies have evaluated the structurally similar convallatoxin found in Convallaria majalis (lily of the valley) for rapid laboratory screening, nor has digoxin immune Fab been tested as an antidote for this ingestion. OBJECTIVE We aimed to (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Regardless of the source, CT exerts cytotoxic effects on a number of cancer cell lines (Felth et al, ; Levrier et al, ; Yang et al, ; Schneider et al, ) but its effects in cancer‐stem like cells is not known. In humans, the serum concentration of CT required to produce symptoms is unknown but in animal models the toxic levels of CT has been reported to be in the range of 18–180 μM (Fink et al, ). Therefore our report that CT can target cells with increased stemness properties at nanomolar concentrations (50–100) makes this drug an interesting candidate for the treatment of chemoresistant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the source, CT exerts cytotoxic effects on a number of cancer cell lines (Felth et al, ; Levrier et al, ; Yang et al, ; Schneider et al, ) but its effects in cancer‐stem like cells is not known. In humans, the serum concentration of CT required to produce symptoms is unknown but in animal models the toxic levels of CT has been reported to be in the range of 18–180 μM (Fink et al, ). Therefore our report that CT can target cells with increased stemness properties at nanomolar concentrations (50–100) makes this drug an interesting candidate for the treatment of chemoresistant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a placebo‐controlled clinical study confirmed their effectiveness against yellow oleander intoxication . However, the digoxin‐specific antibody fragments do not seem to be useful for the intoxication with glycosides from the lily‐of‐the‐valley ( Convallaria majalis ) . Limited shelf‐life and their higher cost make these antidotes available only at special cardiology, or toxicology centers.…”
Section: Drugs With the Major Effects On The Heartmentioning
confidence: 99%
“…316 However, the digoxin-specific antibody fragments do not seem to be useful for the intoxication with glycosides from the lily-of-the-valley (Convallaria majalis). 317 Limited shelf-life and their higher cost make these antidotes available only at special cardiology, or toxicology centers. Correction of possible hypokalemia should be performed as soon as possible and ventricular dysrhythmias may require additional symptomatic treatment.…”
Section: F I G U R Ementioning
confidence: 99%
“…The toxicity (LD 50 ) of cardiac glycoside is about 10 mg /kg upon i.p. injection in mice, [151]. Development of clinically relevant cardiac glycosides could be helped by systematic evaluation of the large family of cardiac glycosides and synthetic analogs available to date.…”
Section: Toxins and Their Target Of Actionmentioning
confidence: 99%